Penerapan E-Commerce dalam Meningkatkan Visibilitas Produk POC Biourine dari Hasil Samping Usaha Peternakan Sapi: Pengabdian - Mimin Septiani; Zakiyah Darajat; Muhammad Arham Yunus; A Mufhida Rezky Amalia Azzahra Hayat; Fadhil Dwi Syahputra; Gunarya Muhammad Rachman; Muh Fadil Mufli (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to enhance the visibility and market reach of liquid organic fertilizer (biourine), a by product of cow farming, through the utilization of e-commerce platforms. The partner, a cattle farmer producing biourine, had limited skills in digital marketing. The program was implemented using the 3P approach, Preparation, Learning, and Strengthening which included socialization, training on product packaging and labeling, e-commerce-based marketing practices, financial recording using Microsoft Excel, assistance in creating an online store account, as well as evaluation and sustainability strategies. The results show that the partner successfully produced properly packaged products and established an online store that has begun to be used for sales transactions. Monitoring of the store’s performance indicated increased marketing activity and greater partner engagement in online selling processes. In addition, collaboration with the village-owned enterprise (BumDes) and the development of social media accounts further expanded the potential distribution of the product both locally and digitally. This program demonstrates that the application of e-commerce can significantly improve product visibility while strengthening the partner’s independence in managing livestock by product enterprises.